The legal capacity of international conventions and laws to legalise e-arbitration - Labanieh, Mohamad Fateh; Hussain, Mohammad Azam; Mahdzir, Nazli (Universiti Utara Malaysia Press, 2021)
Traditional arbitration is not seen as exhaustive anymore and faces several shortcomings in dealing with international commercial disputes. Therefore, the need for a more effective arbitration method to complement the existing traditional method of arbitration in handling domestic and international commercial disputes becomes a pressing necessity. Electronic arbitration (hereinafter referred to as “e-arbitration”) might be the initial step to accomplish this aspired goal. However, e-arbitration has not been regulated yet at the international level. By using doctrinal legal research methodology, this contribution endeavours to examine the legal capacity of international conventions and laws to legalise e-arbitration. Both primary and secondary data are analytically and critically evaluated using content analysis method. It is discovered that the New York Convention 1958 is not legally sufficient to recognise e-arbitration because it was enacted before the emergence of current modern technologies and communication. However, the UNCITRAL Model Laws, such as Electronic Commerce 1996, Electronic Signatures 2001, Model Law on International Commercial Arbitration 1985, and the United Nations Convention on the Use of Electronic Communications in International Contracts 2005, may play a considerable role in recognising e-arbitration in the context of New York Convention 1958. To summarise, several legal gaps need to be addressed; therefore, the study recommends that the international arbitration communities, such as UNCITRAL, should develop an international legal framework to directly and precisely regulate e-arbitration to enhance legal validity of e-arbitration and to provide international harmonisation and uniformity.